2020
DOI: 10.22454/fammed.2020.461348
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mindfulness Skills-Based Training Program for Resident Physicians

Abstract: Background and Objectives: Resident physicians experience a high level of stress. Mindfulness meditation has been shown to offer medical students and physicians a healthier way to relate to daily stressors. We developed and pilot tested a mindfulness training program and assessed its impact on resident physician burnout and resilience. Methods: The residency program offered 17 family medicine residents a 10-hour mindfulness training over the course of 2 months in 2016. Residents were encouraged, but not mandat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 8 publications
3
27
0
1
Order By: Relevance
“… 42 MBSR administered to surgical interns was found to improve mindfulness, reduce stress, and improve well-being. 43 Several studies demonstrated reduced stress and/or burnout after meditation-based MBIs, 44 48 whereas others did not observe an effect. 49 , 50 In a feasibility study of a mindfulness intervention for German residents, the program was rated as highly feasible with no attrition, but included only nine participants and no comparison group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 42 MBSR administered to surgical interns was found to improve mindfulness, reduce stress, and improve well-being. 43 Several studies demonstrated reduced stress and/or burnout after meditation-based MBIs, 44 48 whereas others did not observe an effect. 49 , 50 In a feasibility study of a mindfulness intervention for German residents, the program was rated as highly feasible with no attrition, but included only nine participants and no comparison group.…”
Section: Discussionmentioning
confidence: 99%
“… 51 Several studies included interventions that were structured by residency program with protected didactic time, which improved feasibility. 26 , 47 , 48 One program 26 used moonlighters to cover trainee time, which is costly and requires institutional commitment. In all, there is heterogeneity in the design and implementation of MBIs for residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They noted improvements in burnout, perceived stress, and level of mindful awareness, while having positive influences on residents’ personal lives and clinical practice. 35 Another study for family practice residents utilized the Respiratory One Method (a meditation practice combining breathing and repetition) for stress reduction, with results showing a positive effect on emotional exhaustion. 36 Similarly, in another study, pediatric residents utilized a smartphone application to complete a 10-d program in mindfulness meditation, and completed surveys at the end of the program.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications indicate that healthcare institutions have begun to adopt courses and programs that promote resilience in healthcare professionals [6][7][8][9][10][11]. As the body of research on interventions to combat burnout grows, it is important to assess multiple aspects of implementing such courses in addition to measuring effects on burnout.…”
mentioning
confidence: 99%